If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6 + -1x) = 1x + -4x + -2 (6 * 3 + -1x * 3) = 1x + -4x + -2 (18 + -3x) = 1x + -4x + -2 Reorder the terms: 18 + -3x = -2 + 1x + -4x Combine like terms: 1x + -4x = -3x 18 + -3x = -2 + -3x Add '3x' to each side of the equation. 18 + -3x + 3x = -2 + -3x + 3x Combine like terms: -3x + 3x = 0 18 + 0 = -2 + -3x + 3x 18 = -2 + -3x + 3x Combine like terms: -3x + 3x = 0 18 = -2 + 0 18 = -2 Solving 18 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x+65+57=180 | | 4.5x+46.9=7.6-8.6x | | 2x-30=124 | | -3x-3y=818 | | (7n-6)+2=1 | | 375+12h=280+15h | | -10n+2(.9-9n)=5.8 | | 8x(x-5)=4x-10+3x-30 | | 12x+y=-60 | | -5(7-x+5x)= | | -5n+6=-35n-42-6n | | 16=[2w+w-1] | | 7y+27=6y-3 | | 3(60)-3x=99 | | 50+3x=14 | | 9a-9.4=8a+4.6 | | -6+x=19 | | -2-2x-5x=-37 | | 8(3-2)=104 | | (y^2-7y-5)-(-3y^2+3y-4)= | | 2(5r+45)=20(2r-24) | | 5n+7+n=3n-2+4n(2n+1) | | t=4+3x | | -10-(-5x)=5x | | 3x+11-x=8+4x-5 | | -4.4+6.2=5x-2.9-4x | | x=4+3t | | 2+0.5x=3-5x | | 7-3u^2=1 | | 50+3x=4 | | x+65+57=90 | | 7(9n-4)= |